Aetiology and Risk Factor Analysis of Patients with Chronic Pancreatitis Admitted in a Tertiary Hospital (IAHS Medical Journal, 2023)
Background: Chronic pancreatitis is defined as a continuing inflammatory disease of the pancreas characterized by irreversible morphologic changes that typically cause pain and/or permanent loss of both exocrine and endocrine function. Chronic pancreatitis can result from episodes of acute pancreatitis of any cause, most commonly in those with multiple relapsing episodes of acute pancreatitis. The objective of our study is to determine the aetiology and risk factor in chronic pancreatitis patients admitted in the hospital.Materials and methods: A retrospective observational study was conducted in the Department of Medicine, Maa- Shishu-O-General Hospital, Chattogram from July 2020 to September 2022. Total 29 patients were selected, as presenting in Medicine Department with documented presentation. All data were taken meeting exclusion criteria and analysed.Results: Mean age, weight, waist circumference and BMI is 35.6 year, 57 kg, 32 cm and 24.5 respectively. Almost 2/3 of the patients admitted from urban area and mostly belong to average socioeconomic groups and male are little bit more affected n=15, 51.7%. Maximum cases were non alcoholic n=18, 62.1%. and found raised Triglyceride n=10, 34.5%. Pancreatic calcification found in significant cases n=14, 48.3%.Conclusion: Chronic pancreatitis is one of the common causes of recurrent abdominal pain. Malnutrition and hypertriglyceridimia is the commonest cause in our country and abdominal x-ray have dramatic role in diagnosis and prognosis also.IAHS Medical Journal Vol 5(2), Dec 2022; 2-5